Interface Structure in Friction Welded Joints between Stainless Steel 304 and Mild Carbon Steel - Helmy Purwanto (Journal of Chemical Process and Material Technology, 2022)
Friction welding is a solid-state welding process using heat generated through friction. Dissimilar materials can be joined properly with friction welding. This study is a continuation of the previous study and aimed to determine the interface structure occurred on stainless steel and carbon steel joints. Stainless steel 304 and mild carbon steel are joined with this method at 2000 rpm rotation for 15 seconds and forging time of 5 seconds with a pressure of 5 MPa. The results of a micro-observation using a scanning electron microscope show good bonding in the interface area. The carbon steel is more welded to the stainless steel in the periphery than in the center. The spectrum results of Energy Dispersive X-Ray of the interface show Fe, C and Cr elements content. This is what causes the strong welding bond.